Study on the use of selective catalytic reduction technique for NOx emission reduction in an diesel engine fuelled with Methyl ester of Water Hyacinth. (2022) - Sachuthananthan, B.; Vinoth, R.; Satya Meher, R.; Sandeep, B.; Sudheer Kumar, N.; Deekshith, C.
Abstract: The emission standard is a big challenge to Automobile Manufacturers in bringing down the diesel engine emissions. Use of renewable fuel which substitutes conventional fuel in diesel engine which results in enhanced pollution levels, specifically NOx. In the present work an initiative is made to analyse the efficacy and pollution attributes of diesel power train propelled with Methyl Ester of water Hyacinth(B20) was investigated. Magnesium Oxide (MgO) and Zinc oxide (ZnO) nano additives at various proportions were added to Water Hyacinth biodiesel (B20). To reduce the NOx emission levels an improved methodology named as selective catalytic reduction (SCR) system was used. The experiment was performed with and without SCR to study the NOx emission characteristics. The results revealed that Methyl Ester of Water Hyacinth was found to be proper alternate instead of Diesel fuel without any engine alterations. The Brake thermal Efficiency(BTE) for diesel fuel was 28.4% and for B20 it was 27.1%, for B20 with 100 ppm NAM it was 27.3%. For B20 blend with 100 ppm NAM, the NOx emission was 786 ppm, and this NOx emission reduced to 596 ppm when SCR was used for B20 blend with 100 ppm NAM.